IoT-Based Framework for Connected Municipal Public Services in a Strategic Digital City Context - Danieli Aparecida From; Denis Alcides Rezende; Donald Francisco Quintana Sequeira (IoT)
The use of digital technology resources in public services enhances efficiency, responsiveness, and citizens’ quality of life through improved resource management, real-time monitoring, and service performance. The objective is to create and apply an IoT-based framework for connected municipal public services in a strategic digital city context. The research employed a modeling process validated in a Brazilian city, identifying seven related frameworks and four themes through a bibliometric review. The original framework comprises three constructs, eight subconstructs, and 12 variables, validated through a case study inquiry. The results revealed that the researched city has yet to enlarge IoT into its municipal public services as part of a digital city project initiative. Key recommendations for IoT implementation include prioritizing the preferences of digital citizens, expanding critical services suited for IoT, and updating municipal strategies to incorporate IT resources to streamline decision-making. The conclusion reiterates that the IoT framework for municipal services is effective when actionable information supports strategic planning and decision-making and highlights the transformative potential of IoT in driving more resilient and sustainable cities aligned with citizens’ needs. This approach allows public managers to enhance citizens’ quality of life while improving the efficiency and responsiveness of urban management processes and services.